Entrepreneurial Intentions in University Students: Based on the Analysis of Entrepreneurship Education, Adversity Quotient, Emotional Intelligence and Family Factor - Chairunisa Muchtar, Y; ., Fadli; Qamariah, I (KnE Social Sciences, 2018)
The number of entrepreneurs in Indonesia is approximately 3.1% of the total population (HTTP://www.depkop.go.id 2016). This number is still considered low compared to other countries such as the United States of America at 11.2%. Various efforts are being made to foster the entrepreneurial intention, especially to change the youth’s mindset, who are interested in seeking a job after graduation. This research aims to analyze the effect of entrepreneurship education, adversity quotient, emotional intelligence, and family factor on entrepreneurial intention. Result shows that entrepreneurship education and adversity quotient have a positive and significant effect on entrepreneurial intention. Meanwhile, emotional intelligence and family factor are insignificantly affecting business performance. In general, in order to increase the entrepreneurial intention, it should focus on the improvement of entrepreneurship education and adversity quotient. Keywords: entrepreneurship education, adversity quotient, emotional intelligence, family factor, entrepreneurial intention